Kenmotsu 3-manifolds and gradient solitons - Mofarreh, F.; De, U.C. (Carpathian Mathematical Publications, 2023)
The aim of this article is to characterize a Kenmotsu 3-manifold whose metric is either a gradient Yamabe soliton or gradient Einstein soliton. It is proven that in both cases this manifold is reduced to the manifold of constant sectional curvature. Finally, we verify the obtained results by an example.